The Effect of Independence and Remote Audit on Audit Quality During the Covid-19 Pandemic - Hendrik Suhendri; Adrian Junaidar Handayanto; Tomas Aldi Kelana (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2022)
This study aims to examine the effect of independence and remote audit on audit quality during the covid-19 pandemic. Covid-19 pandemic makes the auditors have difficulties inspect the audited company directly. Remote audit is a way to solve the difficulties. The effectiveness of remote audit still needs more research related to audit quality. Therefore, this research examines the effect of independence and remote audit on audit quality, both partially and simultaneously. The examination the effect of remote audit on audit quality in covid-19 pandemic is the novelty of this research. The samples are selected by purposive sampling method. The data is collected by questionnaire sent to 8 Public Accounting Firms (KAP) in Malang City. The collected data is analyzed by multiple linear regressions. The partial test results show that auditor independence does not affect on audit quality. On other hand, remote audit affects on audit quality in covid-19 pandemic. Simultaneous test results show that independence and remote audit simultaneous has significant and positive effect on audit quality during the covid-19 pandemic.